An exploration of the loneliness experienced by Indonesian students during the COVID-19 pandemic - Afdal, Afdal; Fikri, Miftahul; Nirwana, Herman; Mudjiran, Mudjiran (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Psychological symptoms, including loneliness, and tiredness of being unable to see friends, relatives, as well as co-workers, indefinitely, are one problem faced during the COVID-19 pandemic. This study, therefore, aims to evaluate the extent of loneliness felt during this period, particularly by students, using a descriptive quantitative method, based on the AF loneliness Scale (AFLS). The cross-sectional study was conducted between June 11 and July 29, 2020, through an online survey on Survey Monkey platform. A total of 504 Indonesians aged 12 to 27 years, from several provinces and regions in Indonesia, participated in this study. Subsequently, the data were analyzed using JASP (Jeffrey's Amazing Statistics Program). According to the results, there was a tendency for 49.40% and 33.47% of students to experience symptoms of loneliness in the medium and high categories, respectively. However, there are differences in the symptoms experienced by male and female students. Racial Batak students also experienced more loneliness, compared to other ethnic groups, for instance, Minang, Malay, and Chinese. In addition, students aged between 20 and 23 are more likely to feel loneliness. These findings are useful inputs for certain parties, including school counselors, to discover alternative solutions to help students affected by the COVID-19 pandemic overcome this feeling